In-season internal and external training monotony, strain and acute/chronic workload ratio variations between starters and non-starters of a top elite European soccer team - Oliveira, Rafael (2022)
The aim of this study was two-fold: (a) to describe the in-season variations of training monotony, training strain, and acute: chronic workload ratio (ACWR) through session rated perceived exertion (s-RPE), total distance and high-speed running (HSR); (b) to compare those variations between starters and non-starters. Seventeen professional players from an European First League team participated in this study. They were divided in two groups: starters (n=9) and non-starters (n=8). The players were monitored daily over a 41-week period of competition where 52 matches occurred during the 2015- 2016 in-season. Through the collection of s-RPE, total distance and HSR, training monotony, training strain and ACWR were calculated for each measure, respectively. Data were analysed across ten mesocycles (M: 1 to 10). Results revealed no differences between starters vs non-starters (p>0.05). M6 had a greater number of matches and displayed higher values in monotony (s-RPE, total distance and HSR), strain (only for total distance) and ACWR (s-RPE, TD and HSR). However, the variation patterns for all indexes displayed some differences. In conclusion, the values of both starters and non starters showed small differences between them and thus suggesting that the adjustments of training workloads that had been applied over the season helped to reduce differences according to the player status. Even so, there some variations over the season (microcycles and mesocycles) for the whole team. This study could be used as reference for future coaches, staff and scientists.